Enhancing Delivery of Small‐Molecule‐ and Cell‐Based Therapies for Ovarian Cancer Using Advanced Delivery Strategies. Issue 11 (16th August 2020) - O'Dwyer, Joanne; O'Cearbhaill, Roisin E.; Wylie, Robert; O'Mahony, Saoirse; O'Dwyer, Michael; Duffy, Garry P.; Dolan, Eimear B.
Abstract: Ovarian cancer is the most lethal gynecological malignancy with a global five‐year survival rate of 30–50%. First‐line treatment involves cytoreductive surgery and administration of platinum‐based small molecules and paclitaxel. These therapies are traditionally administered via intravenous infusion, although intraperitoneal delivery has also been investigated. Initial clinical trials of intraperitoneal administration for ovarian cancer indicate significant improvements in overall survival compared to intravenous delivery, but this result is not consistent across all studies performed. Recently, cell‐based immunotherapy has been of interest for ovarian cancer. Direct intraperitoneal delivery of cell‐based immunotherapies may prompt local immunoregulatory mechanisms to act synergistically with the delivered immunotherapy. Based on this theory, preclinical in vivo studies have delivered these cell‐based immunotherapies via the intraperitoneal route, with promising results. However, successful intraperitoneal delivery of cell‐based immunotherapy and clinical adoption of this technique depend on overcoming challenges of intraperitoneal delivery and finding the optimal combinations of dose, therapeutic, and delivery route. The potential advantages and disadvantages of intraperitoneal delivery of cell‐based immunotherapy for ovarian cancer and the preclinical and clinical work performed so far are reviewed. Potential advanced delivery strategies, which may improve the efficacy and adoption of intraperitoneal delivery of therapy for ovarian cancer, are also outlined. Abstract : Intraperitoneal administration of therapy for ovarian cancer holds promise for improved patient outcomes, however, results have been inconsistent to date which may be due to poor delivery strategies. This review focuses on intraperitoneal delivery of small‐molecule‐ and cell‐based immunotherapies and potential advanced delivery strategies are outlined which might improve the adoption of intraperitoneal delivery of therapy for ovarian cancer.